PREFERENSI KONSUMEN TERHADAP PEMBELIAN MANISAN (STUDI KASUS : MANISAN SRI LANGKAT DI KECAMATAN STABAT KABUPATEN LANGKAT PROVINSI SUMATERA UTARA) - Utami Aditya; Suryadi Suryadi; Irada Sinta (LPPM Universitas Malikussaleh - Indonesia, 2023)
Langkat Regency is a center for selling sweets. Sri Langkat Sweets Business is one of theconfectionery businesses located in Stabat District. Sri Langkat Sweets Business wasfounded by Mrs. Salamiah since 2010. At the Sri Langkat Sweets Business, it has 3 typesof packaging, namely clear plastic, standing pouch, and small cup, with types of sweets,namely gelugur, mango and snakefruit, and has 2 flavor variants, namely sweet and sour.The purpose of this study is to determine which attributes are the most dominantconsidered by consumers in purchasing decisions of Sri Langkat Sweets in Stabat Districtand to determine the combination of Sri Langkat Manisan attributes that are consumerpreferences. This study uses conjoint analysis and qualitative descriptive methods. Theresults of this study indicate that the order of attributes that are most considered byconsumers in purchasing Sri Langkat sweets are packaging, type and taste. This can beseen from the respective NPR values, namely packaging (40,155), type (38,119), and taste (21,726). The combination of the Sri Langkat Manisan order which is a consumerpreference with small cup packaging, types of gelugur and sour taste.